Sweating and core temperature in athletes training in continuous and intermittent sports in tropical climate - Rivera-Brown, A. M.; Ramirez-Marrero, F. A.; Frontanés, J.; Rosario, R. A.; Hernández, O. J.; Frontera, W. R. (Archivos de medicina del deporte, 2019)
Higher sweat rate values have been reported during intermittent compared to continuous type exercise in hot conditions in the laboratory. Studies in the training field are scarce.